7th International Symposium on Superalloy 718 and Derivatives (2010) 2010
DOI: 10.7449/2010/superalloys_2010_199_213
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Both γ' Distribution and Grain Size on the Tensile Properties of UDIMET 720Li At Room Temperature

Abstract: The tensile properties of a forged UDIMET 720Li alloy have been investigated at room temperature. The aim of this study was to increase both yield and ultimate tensile stresses using adequate thermal treatments. Classical three steps heat treatments after hot forging were applied: a solution treatment followed by a quench and a two steps aging treatment. Several combinations were investigated: four hours solution treatments, either sub-solvus (1080 C -1120 C) or super-solvus (1160 C); two different cooling rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…8 also compares R65 to data generated by J.R. Vaunois and al. for C&W Udimet 720Li (U720Li) alloy also solution treated at 1080°C for 4 hours [11]. It is observed that the y' particles in R65 are smaller for given ST cooling rate.…”
Section: Intragranular Y' Growth During Overagingmentioning
confidence: 84%
See 2 more Smart Citations
“…8 also compares R65 to data generated by J.R. Vaunois and al. for C&W Udimet 720Li (U720Li) alloy also solution treated at 1080°C for 4 hours [11]. It is observed that the y' particles in R65 are smaller for given ST cooling rate.…”
Section: Intragranular Y' Growth During Overagingmentioning
confidence: 84%
“…C o o l in g r a t e (°C /m in ) Figure 8. y' size evolution as a function of the ST cooling rate for R65 (present study) and for a subsolvus C&W Udimet 720Li alloy [11] Impact of overaging on creep properties…”
Section: Intragranular Y' Growth During Overagingmentioning
confidence: 99%
See 1 more Smart Citation
“…The model results have been tested mostly in powder metallurgy superalloys with grain size up to 55 lm for subsolvus and supersolvus heat treatments. However, for alloys processed by the cast and wrought route (C&W), the supersolvus heat treatment can lead to grain sizes as large as 1 mm [33]. A Hall-Petch constant of 710 MPa lm 1/2 was considered in our model, although this value could differ for other conditions since there is a concomitant alteration in the c 0 microstructure when modifying the grain size.…”
Section: Discussionmentioning
confidence: 99%
“…In the following of the article, those microstructures will be denoted as the "Duplex" and the "Homogeneous" microstructures, respectively. The main microstructural characteristics (average grain size, volume fractions and sizes of primary, secondary and tertiary γ particles and average interparticle spacings) determined by image analyses techniques [7], [8] are detailed in Table 2. The average γ channels width was taken between the smallest γ precipitates.…”
Section: Materials and Microstructure Characterisationsmentioning
confidence: 99%